Dependence of the adsorption height of graphenelike adsorbates on their dimensionality - Weiß, Simon; Gerbert, David; Stein, Arnulf; Feldmann, Sascha; Tegeder, Petra (Physical review, 2018)
Comparing the adsorption heights of various graphene nanoribbons on Cu(111) and Au(111) surfaces to those of graphene and π-conjugated planar organic molecules, we observe that two-dimensional graphene adsorbs much further away from the surface than both one-dimensional graphene nanoribbons and π-conjugated planar molecules—which represent zero-dimensional graphene flakes. We show that this is a direct consequence of the adsorbates' dimensionality. Our results provide invaluable insights into the interplay of Pauli repulsion, pushback effect, and chemical interaction for graphenelike adsorbates of any dimensionality on metal surfaces.